If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-5x + -17) = 3 Reorder the terms: 3(-17 + -5x) = 3 (-17 * 3 + -5x * 3) = 3 (-51 + -15x) = 3 Solving -51 + -15x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '51' to each side of the equation. -51 + 51 + -15x = 3 + 51 Combine like terms: -51 + 51 = 0 0 + -15x = 3 + 51 -15x = 3 + 51 Combine like terms: 3 + 51 = 54 -15x = 54 Divide each side by '-15'. x = -3.6 Simplifying x = -3.6
| 2(4y)-y=-1 | | 8-3=2(x+1) | | B=3/4(21-b) | | (n+7)(11n-2)=18n(2n+1) | | A=21-b | | 4/3(-5.25) | | f(4)=2.0x^2+7.6x^4+5.0 | | f(x)=2.0x^2+7.6x^4+5.0 | | F=5(10)+18 | | 9w+(-31)= | | 11n^2+21n-14=0 | | -9/5x=27 | | q=m*c*changeT | | F=5(4)+18 | | F=5(2)+18 | | X+5a=29+ax-6a | | 2n=-28n-3 | | V=XLT | | 2x-x+112=16x+112 | | 3/e=3/4 | | 5n-6=18 | | 2y-3+y+6=12 | | F=5(3)+11 | | F=5(5)+11 | | 2x+8x+4+x=180 | | 2q+2q-48=180 | | 3d=15d | | F=14(4)+18 | | 2q-26=q+19 | | 9/2*-7/2=47/2 | | 3j-9+13j=-1 | | 4p+64+17p+74=180 |